Bilateral Common Carotid Artery Occlusion in Spontaneously Hypertensive Rats: A Feasible Animal Model for Ocular Ischemic Syndrome. Issue 6 (29th March 2016) - Wang, Yacong; Fan, Yuhua; Zhang, Lihong; Wang, Yi‐Xiang J.; Qi, Wei; Liang, Willmann; Wang, Chunmei; T.W. Yew, David; Ye, Cunxi; Sha, Ou
ABSTRACT: The purpose of this study was to investigate the feasibility of inducing ocular ischemic syndrome in spontaneously hypertensive rats. Hypertensive and normotensive Wistar–Kyoto rats had bilateral occlusion or sham surgery. They were divided into 4 groups: (1) hypertensive‐ischemia, (2) hypertensive‐sham, (3) normotensive‐ischemia, and (4) normotensive‐sham. Four months after the operation, the global changes of the eye and pupillary light reflex were assessed. Then each rat was perfused, and randomly one of the bulbuses oculi was prepared as retinal flat mounts for investigation of vascular changes. The opposite eyeball was prepared as a paraffin section for observation of the linear density of retinal ganglion cells and for thickness measurement. One hypertensive‐ischemia rat had a cataract in one eye and another rat in the same group had bulbus oculi collapse in one eye. The light reflex disappeared in 13.33% of hypertensive‐ischemia rats, and the rest of the hypertensive‐ischemia rats and normotensive‐ischemia rats had slow reflex. Compared with the respective controls, the peripheral retinal vascular network in hypertensive‐ischemia and normotensive‐ischemia rats was sparse; linear density of the retinal ganglion cells was significantly reduced; and the retinal thickness was reduced. Compared with normotensive‐ischemia rats, the hypertensive‐ischemia rats demonstrated more severe changes. After bilateral common carotic artery occlusion, the eyes of hypertensive rats developed various pathological changes similar to those of ocular ischemic syndrome. In conclusion, an animal model for ocular ischemic syndrome can be created by bilateral common carotid artery occlusion in spontaneously hypertensive rats. Anat Rec, 299:806–814, 2016. © 2016 Wiley Periodicals, Inc.